Considerations for successful cancer immunotherapy in aged hosts. (7th November 2016) - Hurez, V.; Padrón, Á. S.; Svatek, R. S.; Curiel, T. J.
Summary: Immunotherapy is now experiencing unprecedented successes in treating various cancers based on new understandings of cancer immunopathogenesis. Nonetheless, although ageing is the biggest risk factor for cancer, the majority of cancer immunotherapy preclinical studies are conducted in young hosts. This review will explore age‐related changes in immunity as they relate to cancer immune surveillance, immunopathogenesis and responses to immunotherapy. Although it is recognized that declining T cell function with age poses a great challenge to developing effective age‐related cancer immunotherapies, examples of successful approaches to overcome this hurdle have been developed. Further, it is now recognized that immune functions do not simply decline with age, but rather change in ways than can be detrimental. For example, with age, specific immune cell populations with detrimental functions can become predominant (such as cells producing proinflammatory cytokines), suppressive cells can become more numerous or more suppressive (such as myeloid‐derived suppressor cells), drugs can affect aged immune cells distinctly and the aged microenvironment is becoming recognized as a significant barrier to address. Key developments in these and other areas will be surveyed as they relate to cancer immunotherapy in aged hosts, and areas in need of more study will be assessed with some speculations for the future. We propose the term 'age‐related immune dysfunction' (ARID) as best representative of age‐associated changes in immunity. Abstract : This is a comprehensive review of age effects on responses to cancer immunotherapy.